2017
DOI: 10.1017/s0007114517001702
|View full text |Cite|
|
Sign up to set email alerts
|

Arginine and aerobic training prevent endothelial and metabolic alterations in rats at high risk for the development of the metabolic syndrome

Abstract: Endothelial function is a key mechanism in the development of CVD. Arginine and exercise are important non-pharmacological strategies for mitigating the impact of metabolic changes in the metabolic syndrome, but the effect of their combined administration is unknown. Thus, the aim of this study was to investigate the isolated and combined effects of aerobic training and arginine supplementation on metabolic variables and vascular reactivity in rats at high risk for developing the metabolic syndrome. Wistar rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 84 publications
4
4
0
Order By: Relevance
“…In the present study, we demonstrated that the pulp of Camu-camu reduced body weight and epididymal and visceral fat, such as reduced fat deposited in the face, heart and liver, in addition to decrease the inflammatory proteins [16]. Several experimental studies have shown that exercise combined with continued dieting results in reduced adiposity, lipid profile and reduction of biochemical parameters in rats [17][18][19].…”
Section: Introductionsupporting
confidence: 55%
“…In the present study, we demonstrated that the pulp of Camu-camu reduced body weight and epididymal and visceral fat, such as reduced fat deposited in the face, heart and liver, in addition to decrease the inflammatory proteins [16]. Several experimental studies have shown that exercise combined with continued dieting results in reduced adiposity, lipid profile and reduction of biochemical parameters in rats [17][18][19].…”
Section: Introductionsupporting
confidence: 55%
“…The antiplatelet effect observed is probably related to the association of an enhancement of NO production and a reduction in oxidative stress and inflammatory cytokines, resulting in a reduction in platelet TXA 2 production and platelet activation and aggregation (Figure 5). Similar results were observed by our group in vascular beds [9, 19].…”
Section: Discussionsupporting
confidence: 92%
“…These results point out the antiplatelet effects when arginine supplementation is associated with aerobic exercise. Our research group [19] showed a vasodilator activity associated with an improvement of endothelial function and an increased NO bioavailability, observed in the group that received arginine supplementation, as well as in the aerobic exercise group treated with fructose. On the other hand, no additive effect in vascular relaxation in the interventions associated was observed [19].…”
Section: Discussionmentioning
confidence: 99%
“…This was concomitant with a marked increase in cold-induced glucose oxidation in men of European descent only. As with endothelial function, these findings have been supported by data in rats [13] and earlier findings in humans at moderate doses of arginine [16].…”
Section: Insulin Sensitivity and The Diabetes Risksupporting
confidence: 72%
“…For instance, in fructose-fed rats, supplemental arginine prevented the impairment of endotheliumdependent vasodilation and hyper-reactivity to phenylephrine, to the same degree as aerobic training [13]. Both treatments increased plasma nitrite, indicative of increased eNOS activity.…”
Section: Endothelial Functionmentioning
confidence: 93%